Design of the extruder drive motor and its HNTSM speed control with disturbance observer. Issue 1 (February 2021) - Zhang, Jiacheng; Fan, Yuanxun; Lu, Pengcheng; Cao, Dawei; Liu, Zhikang
Abstract: In order to meet the requirements of 25kW rated power and 1500r/min rated speed required by the extrusion process of polyester fiber composite materials, a PMSM suitable for this working condition was designed to complete the driving task of the extruder. The geometric model of the motor was established using RMxprt, and the load operation state of the motor was simulated by Maxwell. The motor speed was controlled by a HNTSM control scheme with a disturbance observer, and based on Twin builder and simulink coupled simulation. The simulation results show that the motor can reach the required rated power and rated speed. HNTSM control with disturbance observer is more robust than HNTSM and PID control, and can suppress the jitter caused by sliding mode control. However, compared with PID control, there is still some jitter.